Signatures of Sixfold Degenerate Exotic Fermions in a Superconducting Metal PdSb2 - Kumar, Nitesh; Yao, Mengyu; Nayak, Jayita; Vergniory, Maia G.; Bannies, Joern; Wang, Zhijun; Schroeter, Niels B. M.; Strocov, Vladimir N.; Muechler, Lukas; Shi, Wujun; Rienks, Emile D. L.; Manes, J. L.; et al. (Advanced Materials, 2020)
Multifold degenerate points in the electronic structure of metals lead to exotic behaviors. These range from twofold and fourfold degenerate Weyl and Dirac points, respectively, to sixfold and eightfold degenerate points that are predicted to give rise, under modest magnetic fields or strain, to topological semimetallic behaviors. The present study shows that the nonsymmorphic compound PdSb2 hosts six-component fermions or sextuplets. Using angle-resolved photoemission spectroscopy, crossing points formed by three twofold degenerate parabolic bands are directly observed at the corner of the Brillouin zone. The group theory analysis proves that under weak spin–orbit interaction, a band inversion occurs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: angle-resolved photoemission spectroscopy; electronic structure; first principle calculations; multifold degenerate points; topological materials